Food Source Plants of Coastal Communities in Galela, North Halmahera - Patty, Zeth; Kastanja, Ariance Yeane (MultiTech Publisher, 2024)
This study aims to identify food source plants and parts that are utilized, as well as their processing in the Galela Community. The interview method with the help of questionnaires was carried out to collect data including; types of plants, parts of plants that are utilized and processing methods. Respondents were housewives totaling 65 respondents. The results showed that there are 34 plant species from 20 families that are used as food sources, both cultivated and found in nature, with consumed parts namely leaves, stems, flowers, fruits, tubers, rhizomes, and leaf buds. The leaves, flowers, and young stem are mostly consumed as vegetables. Bananas and yams that are consumed as staple food are usually processed by boiling, coconut milk or frying.